Effect of high pressure treatment on metabolite profile of marinated meat in soy sauce. (1st February 2018) - Yang, Yang; Ye, Yangfang; Wang, Ying; Sun, Yangying; Pan, Daodong; Cao, Jinxuan
Highlights: The profile of marinated meat in soy sauce was dominated by 26 metabolites. Glutamate, sugars, nucleotides, anserine, lactate and creatine increased under HP. HP contributed to improve the taste of marinated meat in soy sauce. Effect of HP (150 and 300 MPa) on metabolites was not dependent on pressure level. Abstract: Marinated meat in soy sauce was produced using hind leg by washing, rubbing salt, marinating with soy sauce and spices, and air dry-ripening for 15 d. The effect of high pressure (HP) (150 and 300 MPa for 15 min) on the metabolite profiles of products was characterized using 1 H NMR and multivariate data analysis. The results showed that the metabonome was dominated by 26 metabolites, including amino acids, sugars, organic acids, nucleic aides and their derivatives. PC1 and PC2 explained a total of 75.4 and 11.9% of variables, respectively. HP treatments increased most of the metabolites, especially PC1, glutamate, sugars, nucleotides, anserine, lactate and creatine compared to the control. The increase of metabolites under HP was not dependent on pressure level except for alanine, lactate, acetate, formate, fumarate, glucose and 5′-IMP. These findings demonstrated that HP treatment at 150 MPa was economical to improve the taste of marinated meat in soy sauce.